Methods to improve efficacy of orally administered bioactive peptides using bovine colostrum as an exemplar. - Raymond John Playford (Public Library of Science (PLoS), 2021)
Background Oral administration of bioactive peptides has potential clinical advantages, but its applicability is limited due to gastric and pancreatic enzyme proteolysis. Objective To examine whether the co-packaging of bovine colostrum (BC), a rich source of IgG, immune and growth factors, with the food additives trehalose (carbohydrate), stearine (fat), casein (protein present in BC) or soy flour (plant based with high protease inhibitory activity) enhances the stability of BC against digestion. Design Samples alone and in combination (BC+ 10% wt/wt trehalose, stearine, casein or soy) were exposed to HCl/pepsin, followed by trypsin and chymotrypsin ("CT"). Assessment of proliferation used gastric AGS cells (Alamar blue), IgG function measured bovine IgG anti-E.coli binding and ELISAs quantified growth factor constituents. In vivo bioassay assessed ability of BC alone or with soy to reduce injury caused by dextran sodium sulphate (DSS, 4% in drinking water, 7 days, test products started 2 days prior to DSS). Results Proliferative activity of BC reduced 61% following HCl/pepsin and CT exposure. This was truncated 50% if soy was co-present, and also protected against loss of total IgG, IgG E.coli binding, TGFβ, lactoferrin and EGF (all P<0.01 vs BC alone). Co-packaging with trehalose was ineffective in preventing digestion whereas casein or stearine provided some intermediate protective effects. Rats given BC alone showed beneficial effects on weight gain, disease activity index, tissue histology and colonic MPO. Soy alone was ineffective. BC+ soy combination showed the greatest benefit with a dose of 7 mg/kg (6.4 BC + 0.6 soy flour) having the same degree of benefit as using 20 mg/kg BC alone. Conclusion Soy, and to a lesser extent casein, enhanced the biostability of BC against digestive enzymes. Co-packaging of BC with other food products such as soy flour could result in a decreased dose being required, improving cost-effectiveness and patient compliance.